Synthesis and Characterization of Magnesium Oxide from Salt Waste (Bittern) - Rizkyquina Arsya Amelia; Listyorini Hastuti; Caecilia Pujiastuti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Salt waste (bittern) is a byproduct of the salt processing industry that is rich in magnesium, but is often not optimally utilized and is discharged into the environment. This study aims to produce magnesium oxide (MgO) from salt waste through a synthesis and characterization process. The synthesis process begins with the precipitation of magnesium hydroxide (Mg(OH)2) using sodium hydroxide (NaOH), which is then calcined at various temperatures and times to convert it to MgO. The calcination temperature variations used include 300–700°C, and calcination times between 2 and 6 hours. Product characterization was carried out using the XRF method for chemical composition analysis, XRD to determine the crystal structure, and SEM to observe particle morphology. The results showed that calcination temperature and time have a significant effect on MgO formation. The optimal temperature to produce the highest MgO is 500°C, with the best calcination time of 3 hours. Under these conditions, the resulting MgO has a crystal size of approximately 42 nm and a uniform and porous particle morphology. This research proves that salt waste has great potential to be utilized as a raw material for magnesium oxide, which not only reduces environmental pollution but also provides economic added value. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water